Faktor Kunci Loyalitas: Analisis Kualitas Layanan, Produk Beragam, dan Kepuasan Pelanggan - Permadi, Edo Galih; Muzakki, Muzakki; Murti, Agung Bayu; Waras , Waras (Universitas Sains dan Teknologi Komputer, 2024)
This study examines the factors that influence customer loyalty, focusing on service quality, product variety, and customer satisfaction. Through quantitative analysis, this study identifies the direct influence of each variable on customer loyalty. The results show that customer satisfaction has the most significant impact, where higher levels of satisfaction consistently increase loyalty. Product variety also contributes substantially, indicating the importance of offering a wide range of product choices to retain customers. Service quality has a positive impact on loyalty, although with a smaller effect compared to satisfaction and product variety. These findings emphasize the importance of improving service quality, expanding product variety, and prioritizing customer satisfaction as key strategies to drive sustainable customer loyalty. These strategies can be the basis for building long-term relationships between companies and customers.